MDA5 signaling induces type 1 IFN- and IL-1-dependent lung vascular permeability which protects mice from opportunistic fungal infection - Davis, Michael J.; Martin, Rachel E.; Pinheiro, Giovana M.; Hoke, Elizabeth S.; Moyer, Shannon; Mayer-Barber, Katrin D.; Chang, Yun C.; Kwon-Chung, Kyung J. (Frontiers in Immunology, 2022)
Lungs balance threat from primary viral infection, secondary infection, and inflammatory damage. Severe pulmonary inflammation induces vascular permeability, edema, and organ dysfunction. We previously demonstrated that poly(I:C) (pICLC) induced type 1 interferon (t1IFN) protected mice from Cryptococcus gattii (Cg) via local iron restriction. Here we show pICLC increased serum protein and intravenously injected FITC-dextran in the lung airspace suggesting pICLC induces vascular permeability. Interestingly, pICLC induced a pro-inflammatory signature with significant expression of IL-1 and IL-6 which depended on MDA5 and t1IFN. Vascular permeability depended on MDA5, t1IFN, IL-1, and IL-6. T1IFN also induced MDA5 and other MDA5 signaling components suggesting that positive feedback contributes to t1IFN dependent expression of the pro-inflammatory signature. Vascular permeability, induced by pICLC or another compound, inhibited Cg by limiting iron. These data suggest that pICLC induces t1IFN which potentiates pICLC-MDA5 signaling increasing IL-1 and IL-6 resulting in leakage of antimicrobial serum factors into lung airspace. Thus, induced vascular permeability may act as an innate defense mechanism against opportunistic fungal infection, such as cryptococcosis, and may be exploited as a host-directed therapeutic target.